(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Gender linguistics is an interdisciplinary field that examines the relationship between language and gender, focusing on how linguistic forms reflect, construct, and reinforce gender identities and social inequalities. This article explores the theoretical foundations of gender linguistics, key approaches to the study of language and gender, linguistic features associated with gendered speech, and contemporary debates in the field. Particular attention is paid to the role of language in maintaining power relations and to the impact of globalization and digital communication on gendered discourse. The study demonstrates that gender is not merely reflected in language but actively produced through linguistic interaction, making gender linguistics a crucial area of modern sociolinguistic research.